2013
DOI: 10.1177/0310057x1304100613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Anaesthesia Information Video on Preoperative Maternal Anxiety and Postoperative Satisfaction in Elective Caesarean Section: A Prospective Randomised Trial

Abstract: Video-based patient information supplementing clinician interview has been shown to reduce anxiety and improve satisfaction in patients undergoing procedures. In Queensland more than 90% of caesarean sections are performed under regional anaesthesia. We aimed to assess the effect of using an information video about neuraxial blockade in patients having regional anaesthesia for elective caesarean section. Subjects were randomised to undergo usual care (Group C), or to view a video and undergo usual care (Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 12 publications
3
34
0
2
Order By: Relevance
“…We also found that video presentation was more effective than verbal and written patient educations in improving patient satisfaction. This is in line with the findings of some previous studies (6,9,11,14) and contrary to the findings of some other ones (15,17,22). The greater effectiveness of video presentation may be due to the presentation of the steps and the environment of endoscopy during video presentation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We also found that video presentation was more effective than verbal and written patient educations in improving patient satisfaction. This is in line with the findings of some previous studies (6,9,11,14) and contrary to the findings of some other ones (15,17,22). The greater effectiveness of video presentation may be due to the presentation of the steps and the environment of endoscopy during video presentation.…”
Section: Discussionsupporting
confidence: 87%
“…However, Pehlivan et al (2011) reported the greater effectiveness of verbal education compared with written one (9). Moreover, although some studies reported that video-based education is more effective than written or verbal education (18,19,21,23), other studies found no significant difference between video-based and other types of patient education (15,17,24). Given the conflicting findings of the previous studies, the present study was conducted to examine the effects of video-and pamphlet-based patient education on anxiety and satisfaction among candidates for gastroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Un document retraçant les étapes du parcours de soins est utile. L'information préalable (visuelle sous forme de vidéos) peut diminuer l'anxiété lors de la césarienne elle-même bien que cela ne soit pas toujours observé [8]. L'information améliore aussi la relation soignant-soignée et augmente la satisfaction maternelle, voire celle du couple.…”
Section: Avant L'interventionunclassified
“…[5,6] Anxiety is highly prevalent during pregnancy and the mode of delivery may also be related to anxiety thus elective cesarean section (CS) patients are vulnerable to high anxiety levels. [7,8] Focusing on decreasing maternal anxiety has shown to have favorable effects on fetal health and maternal satisfaction in elective CS patients. Multimedia-based preoperative education to enhance patient knowledge improves anxiety and satisfaction rates in different clinical scenarios but the ideal method and timing of effective preoperative information to decrease pre-and perioperative anxiety remains unclear.…”
Section: Introductionmentioning
confidence: 99%